2005
DOI: 10.1200/jco.2005.03.170
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Study of Matrix Metalloproteinase Inhibitor Prinomastat in Non–Small-Cell Lung Cancer

Abstract: Prinomastat does not improve the outcome of chemotherapy in advanced NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(105 citation statements)
references
References 17 publications
0
104
0
1
Order By: Relevance
“…No survival benefit has been noted when 5 or 15 mg bid prinomastat has been added to standard chemotherapy such as paclitaxel plus carboplatin (20) or gemcitabine plus cisplatin in these studies (21). One explanation for lack of tumor response in these studies could be that the doses of prinomastat were inadequate.…”
Section: Discussionmentioning
confidence: 79%
“…No survival benefit has been noted when 5 or 15 mg bid prinomastat has been added to standard chemotherapy such as paclitaxel plus carboplatin (20) or gemcitabine plus cisplatin in these studies (21). One explanation for lack of tumor response in these studies could be that the doses of prinomastat were inadequate.…”
Section: Discussionmentioning
confidence: 79%
“…The MMPI, marimastat, that has selective affinity for MMP-2/-9, was evaluated in a phase III trial enrolling patients with platinum resistant, recurrent OvCa. Although the trial was not formally published, abstracts and reviews (11) reported that treatment with marimastat did not block tumor growth or improve survival, a result that is in line with other unsuccessful trials of MMPI in cancer (8,10). The data presented here, demonstrating that MMP-2 is important for adhesion and early metastasis, explain at least partially, why marimastat failed in the treatment of OvCa - patients treated with marimastat had widely metastatic tumors that are less dependant on MMPs for continued growth and survival.…”
Section: Figurementioning
confidence: 77%
“…In spite of these revelations, no MMPs have been identified as being absolutely required for neoplastic cell migration/invasion into ectopic tissue compartments in vivo. Based upon their perceived importance as mediators of ECM remodeling, clinical trials assessing efficacy of broad spectrum MMP inhibitors (MMPI) in patients with solid tumors, including non-small cell lung (8), pancreatic (9), gastric (10), and OvCas (11), were undertaken in patients with recurrent, metastatic, chemotherapy-resistant tumors. Unfortunately, none of the MMPI evaluated improved patient survival (12).…”
Section: Introductionmentioning
confidence: 99%
“…2 Additionally, the clinical trials in small-cell lung carcinomas had to be terminated prematurely. 3 This failure led to the early cessation of ongoing trials, and to reconsideration of the merit of a variety of MMPIs in clinical development by a number of pharmaceutical companies. 4 --6 The molecular mechanism behind this disappointing outcome of MMP inhibition is still unclear, given the demonstrable efficacy of MMPI in pre-clinical trials.…”
Section: Introductionmentioning
confidence: 99%